Participation patterns of women in entrepreneurship: A focus on franchising ventures - Mohd. Salleh , Norliza; Ismail, Kamariah; Abu Talib, Noraini; Abu Hamid, Nik Intan Norhan; Sh. Ahmad, Fauziah (Universiti Teknologi Malaysia, 2006)

(untitled)
The number of women involved in business sector is a growing phenomenon worldwide. Despite this scenario, the involvement of women in business particularly in franchising business is not being studied thoroughly and systematically. Franchising is known as a mean to provide opportunities to minorities and women who have interests to venture in business. This study attempts to look into a few questions related to women involvement in franchising venture. The questions are: 1) what is the pattern of women’s participation in franchise business 2) problems faced by franchisees in the franchise business and 3) what are the role of government in promoting and assisting the women in their franchise business. The study is conducted by taking samples of 24 women franchisors and 31 franchisees all over Malaysia participating in franchise business. The findings show that there are less women franchisors in the top ad ministrative positions such as the managing director, chairman and the general manager. The top three problems identified by franchisees are limited control in managing the franchise business, the power to terminate the agreement by franchisees and tough competition facing them as franchisees. The government is really showing their commitment and doing their part in supporting the franchise business by giving loans and setting up agencies which seriously looked into the matters of franchising in Malaysia.